1998
DOI: 10.1084/jem.187.7.1019
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Granulocyte–committed Cells Can Be Driven to Acquire Dendritic Cell Characteristics

Abstract: Polymorphonuclear granulocytes (PMNs) are thought to fulfill their role in host defense primarily via phagocytosis and release of cytotoxic compounds and to be inefficient in antigen presentation and stimulation of specific T cells. Dendritic cells (DCs), in contrast, are potent antigen-presenting cells with the unique capacity to initiate primary immune responses. We demonstrate here that highly purified lactoferrin-positive immediate precursors of end-stage neutrophilic PMN (PMNp) can be reverted in their fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
126
3
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 46 publications
11
126
3
6
Order By: Relevance
“…Such a lineage switch may occur under specified conditions, such as inflammation, because GM-CSF, TNF-␣, IFN-␥, IL-4, and M-CSF are inflammatory cytokines. Oehler et al 46 demonstrate that neutrophil granulocytecommitted cells acquire dendritic cell features in the presence of GM-CSF, IL-4, and TNF-␣. Our results indicated that when CD15 ϩ CD14 Ϫ cells were cultured with GM-CSF, TNF-␣, IFN-␥, and IL-4, the resultant cells exhibited a partial appearance of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Such a lineage switch may occur under specified conditions, such as inflammation, because GM-CSF, TNF-␣, IFN-␥, IL-4, and M-CSF are inflammatory cytokines. Oehler et al 46 demonstrate that neutrophil granulocytecommitted cells acquire dendritic cell features in the presence of GM-CSF, IL-4, and TNF-␣. Our results indicated that when CD15 ϩ CD14 Ϫ cells were cultured with GM-CSF, TNF-␣, IFN-␥, and IL-4, the resultant cells exhibited a partial appearance of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental data suggests that neutrophils have the potential to trans-differentiate into DCs (Oehler et al, 1998;Yamashiro et al, 2000;Iking-Konert et al, 2001a). Therefore, neutrophils appear to have different phenotypic characteristics depending on a variety of factors, including the survival duration.…”
Section: Discussionmentioning
confidence: 99%
“…Human peripheral blood and inflammatory neutrophils express functional B7-1-like molecules, and the expression of these molecules is upregulated by the neutrophils of patients with chronic inflammatory disease or Wegener's granulomatosis (Windhagen et al, 1999;Iking-Konert et al, 2001b. The in vitro generation of dendritic cell (DC)-like cells from immediate precursors of mature neutrophils (Oehler et al, 1998) or neutrophils from the peripheral blood using cytokines has also been reported (Yamashiro et al, 2000;IkingKonert et al, 2001a). Neutrophils and immature DCs co-localize during pathogenic challenge (van Gisbergen et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Le neutrophile au repos exprime uniquement les molécules du CMH de classe I. Le neutrophile activé en présence d'IFN-γ, GM-CSF, TNF-α, IL-4 va se modifier et exprimer à sa surface le CMH de classe II, CD83, CD40 et CCR6 mais, de plus, les molécules de co-stimulation CD80 (B7-1) et CD86 (B7-2), critères définissant une cellule dendritique [22][23][24]. Certains neutrophiles au repos possèdent déjà, dans leur cytoplasme, ces molécules pré-stockées ; ils en possèdent éga-lement d'autres comme CD20, 21, 22, marqueurs de lymphocytes B [25].…”
Section: Présentation Du Peptide Antigénique Par Le Neutrophileunclassified
“…La présentation antigénique par le neutrophile est efficace puisqu'il peut alors activer les lymphocytes T mis en présence du peptide antigénique par ce neutrophile, que ce soit un peptide conventionnel ou un superantigène [26][27][28]. Le neutrophile, devenu une cellule de type dendritique, semble être 10 000 fois plus efficace à pré-senter l'antigène qu'une cellule dendritique classique en provenance de monocytes [23]. Le neutrophile peut aussi présenter un antigène peptidique en utilisant la voie du CMH de classe I [29].…”
Section: Présentation Du Peptide Antigénique Par Le Neutrophileunclassified